Postpartum intrauterine device placement: a patient-friendly option - Carrie Cwiak; Sarah Cordes (BMC, 2018)
Abstract Women in the United States are increasingly choosing an intrauterine device (IUD) for contraception. Since the postpartum period is an important time to consider a patient's need for contraception, offering postpartum IUD placement is considered best practice. Effective implementation of postpartum IUD placement occurs within a context of shared decision making wherein patients are given full information about all options and guided to methods that best fit their lifestyle. Within this context, both the non-hormonal and hormonal IUDs are safe, highly effective, well tolerated, and convenient options. National guidelines support the placement of IUDs, whether immediate (within 10 min of placental delivery) or early postpartum (after 10 min and before 4 weeks after placental delivery), for breastfeeding or non-breastfeeding women. Studies have noted increased IUD expulsion rates, but equivalent IUD usage rates with immediate or early postpartum placement. Postpartum placement requires additional skills that can be easily taught. Finally, successful implementation of a postpartum IUD placement program can be accomplished in hospitals using a team-based approach.